NEW CONCEPTS IN INDEXING - SHANK, R (Bulletin of the Medical Library Association, 1965)
Recent trends in indexing emphasize mechanical, not intellectual, developments. Mechanized operations have produced indexes in depth (1) of information on limited areas of science or (2) utilizing limited parameters for analysis. These indexes may include only citations or both useful data and citations of source literature. Both keyword-in-context and citation indexing seem to be passing the test of the marketplace. Mechanical equipment has also been successfully used to manipulate EAM cards for production of index copy. Information centers are increasingly being used as control devices in narrowly defined subject areas. Authors meet growing pressures to participate in information control work by preparing abstracts of their own articles. Mechanized image systems persist, although large systems are scarce and the many small systems may bring only limited relief for information control and retrieval problems. Experimentation and limited development continue on theory and technique of automatic indexing and abstracting.